Surface Properties of Graphene Functionalized TiO2/nHA Hybrid Coatings Made on Ti6Al7Nb Alloys via Plasma Electrolytic Oxidation (PEO) - Yigit, Oktay; Ozdemir, Niyazi; Dikici, Burak; Kaseem, Mosab (Mdpi, 2021)
Nano-hydroxyapatite (nHA)-matrix coatings containing graphene nanosheets (GNS)-nHA were coated on Ti6Al7Nb alloys by plasma electrolytic oxidation (PEO) treatment for the improvement of their surface properties. Crystallographic properties, functional groups, and elemental analysis of coatings were characterized by XRD, ATR-FTIR, and EDS analysis. Surface morphological changes of the coated surfaces were investigated by AFM and SEM. The electrochemical corrosion behavior of the coatings was examined by using the potentiodynamic scanning (PDS) tests under in-vitro conditions in simulated body fluid (SBF). The results showed that the GNS was successfully deposited in ceramic matrix coatings on Ti6Al7Nb alloys. Also, the microstructural observations revealed that the coatings have a porous and rough structure. The XRD and ATR-FTIR quantitative analysis have proved the appearance of HA and GNS in the coating layers. An increase in the coating thickness, surface hardness, and anatase/rutile transformation rate was determined, while the GNS ratio in the coating layers was increased. The microhardness of the nHA coating reinforced with 1.5 wt% GNS was measured at 862 HV, which was significantly higher than that of GNS-free (only nHA) coating (584 HV). The best in-vitro resistance to corrosion in SBF was observed in the nHA/1.5GNS wt% coating.
Keywords: graphene; PEO; Ti6Al7Nb; hydroxyapatite; in-vitro corrosion